Catholic Pentecostalism and the paradoxes of Africanization : processes of localization in a Catholic Charismatic movement in Cameroon - Lado, Ludovic, 1970- (Studies of Religion in Africa, 2009)
The anthropological literature on religious innovation and resistance in African Christianity tended to focus almost exclusively on what have come to be known as African Independent Churches. Very few anthropological studies have looked at similar processes within mission churches. Through an ethnographic study of localizing processes in a Charismatic movement in Cameroon and Paris, the book critically explores the dialectics between 'Pentecostalization' and 'Africanization' within contemporary African Catholicism. It appears that both processes pursue, although for different purposes, the missionary policy of dismantling local cultures and religions: practices and discourses of Africanization dissect them in search of 'authentic' African values; Charismatic ritual on the other hand features the dramatization of the defeat of local deities and spirits by Christianity.